The effect of wild vetch seed (vicia ervilia) with treatment on growth performance and carcass traits in broiler chickens - Mehmet Avcı; Rahmi Kanat (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the effects of Ihe raw. soaking, boiled, roasting wild vetch seed (Vicia ervilia L Wild) added to feed al 4%, %7, 10% levels on the broiler performance and carcass parts. Totally, 390 broiler chicks were used in the study. Each treatment was added to diet at three levels (4 %, 7 % and 10%) in the experimenl performed with one control, one raw (non-processing), and three processing (soaking, boiled and roasting ) wild vetch seed (Vicia ervilia L Wild). Each treatment was replicated 3 times. The experiment continued at six weeks. The highest live we-ighis were obtained in groups control and raw (1349.46 and 1283.16 g. respectively) There were no significant differences regarding live weight in soaking, boiled and roasting groups (1248.00, 1250.40, 1231.09 g, respectively). Values of live weight in all groups at the levels of 4 % and 7 % were significantly higher (p<0.01) than that of 10 %. Feed consumption in group raw was significantly lower (p<0.01) than that of control. In addition; feed consumption in soaking, boiled and roasting groups were also significantly lower (p<0.0t) than that of control and raw groups. Feed consumption at 4 % and 7 % levels were higher than that of groups at 10 % levels. Feed conversion were similar in groups control, raw. soaking and boiled. However, it was lower in group roasting. Wild vetch seed levels had no effect on teed conversion in all groups. In conclusion; it was concluded thai raw wild vetch seed at 4% level could be used in broiler feed.